Rotational representation of a plate made of Grioli-Toupin material - Jemielita, G.
A solenoidal part of displacement field appearing in a plate made of material with constraints has been determined. The semi-inverse method has been applied to description. The results being obtained together with the already known biharmonic representation (Jemielita, 1992)might be useful in a new micropolar plate theory formulation.
Keywords: BOUNDARY CONDITIONS; NUMERICAL METHODS; PARTIAL DIFFERENTIAL EQUATIONS; TENSORS; VECTORS